What Is the Best Lens? Comparing the Resolution Power of Genome-Derived Markers and Standard Barcodes - Conti, Angela (Microorganisms, 2021)
Fungal species delimitation was traditionally carried out with multicopy ribosomal RNA (rRNA) genes, principally for their ease of amplification. Since the efficacy of these markers has been questioned, single-copy protein-encoding genes have been proposed alone or in combination for Multi-Locus Sequence Typing (MLST). In this context, the role of the many sequences obtained with Next-Generation Sequencing (NGS) techniques, in both genomics and metagenomics, further pushes toward an analysis of the efficacy of NGS-derived markers and of the metrics to evaluate the marker efficacy in discriminating fungal species. This paper aims at proposing MeTRe (Mean Taxonomic Resolution), a novel index that could be used both for measuring marker efficacy and for assessing the actual resolution (i.e., the level of separation) between species obtained with different markers or their combinations. In this paper, we described and then employed this index to compare the efficacy of two rRNAs and four single-copy markers obtained from public databases as both an amplicon-based approach and genome-derived sequences. Two different groups of species were used, one with a pathogenic species of Candida that was characterized by relatively well-separated taxa, whereas the other, comprising some relevant species of the sensu stricto group of the genus Saccharomyces, included close species and interspecific hybrids. The results showed the ability of MeTRe to evaluate marker efficacy in general and genome-derived markers specifically.